Hydraulic and Geomorphic Impacts of Dam Removal on the Upper Baraboo River, Wisconsin - Greene, Samantha L. (My University, 2010)
Over time, human interaction with space and place has led to shifts in cultural dominance and modes of subsistence. Societies depend on the access to particular natural resources for subsistence, mainly soil, water and timber. This research examines, 1) a brief history of human settlement within the Baraboo River watershed and the drivers behind the shifts of cultural dominance as related to the dependence on soil, water and timber, and, 2) an in-depth study of how society today adapts to a changing natural resources, namely water through the removal of small, hydropower dams. Often in human history, societies prosper and fail depending on their ability to adapt to climate-driven shifts in natural resource availability. However, with the arrival of modern Native Americans and Euro-Americans, shifts in natural resource availability results primarily from the exploitation of environmental services. An illustration of the human-driven alteration of a natural resource is the building and removal of dams along the Baraboo River. This research studies hydraulic and geomorphic responses to the 2001 removal of the La Valle dam from the Baraboo River. Examination of longitudinal profile adjustments and hydraulic response to a 500-year flood using stream surveys from the Flood Insurance Survey, Martin Doyle, the Sauk County Land Conservation Office, and the author show significant changes in channel form continued to occur several years after the removal of the dam. Between 36-39% of stored reservoir sediments were transported downstream since the 500-year flood, involving incision upstream of the dam site and aggradation downstream of the dam site. These bed adjustments created a smoother longitudinal profile; however, a grade control structure at the dam site further appears to strongly influence stream hydraulics and may result in renewed sediment storage within the old reservoir. This research reinforces the need for more studies which examine fluvial response to dam removal at larger spatial and temporal scales. With a better understanding of fluvial response to dam removal, watershed managers and planners can better protect our safety and the quality of our natural resources.
Includes figures, maps, photographs, bibliography
Keywords: Dam removal; Geomorphology; Hydraulics; Baraboo River